Antimicrobial activity of compounds isolated from Lippia javanica (Burm.f.) Spreng and Hoslundia opposita against Mycobacterium tuberculosis and HIV-1 reverse transcriptase - Lall, Namrita (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2010.